Precocious puberty in McCune-Albright syndrome: a case report - Rianti Puji Lestari; Retno Sutomo; Madarina Julia (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
McCune-Albright syndrome (MAS) is a rare disease characterized by a triad of fibrousdysplasia, cafe-au-lait spots and peripheral precocious puberty. We reported a 5-year-8-month old girl with MAS who has been followed-up for 2 years and 8 months. Shewas referred to pediatric endocrinology clinic in our hospital for vaginal bleeding at ageof 2 years 11 months. She had peripheral precocious puberty, i.e. increased estrogenlevel associated with very low gonadotropins, and cafe-au-lait spots on her face and wasdiagnosed as MAS. The patient was treated with estrogen receptor blocker (tamoxifen).She had no menses during the 2 years and 8 months of tamoxifen treatment. Her growthrate and bone maturation were also in normal ranges. However, at the end of tamoxifentreatment she had an episode of vaginal bleeding so that we had to change to othertreatment modalities.